A SPINNING TOP? KAZAKHSTAN'S MULTIVECTORISM WITH OTHER MIDDLE POWER STATES - Brosius, Logan (School of Sciences and Humanities, 2023)
Research surrounding the Republic of Kazakhstan foreign policy often assumes the state’s capture by or capitulation to foreign forces, which lead to further conclusions regarding the extent of Kazakhstan’s sovereignty. Similar claims have also abounded in other research focused upon middle power states – namely, that they do not execute their foreign policy on an independent basis or from endogenous stakeholders. The present thesis instead argues that the Republic of Kazakhstan’s continued use of multivectorism between its partners, large and small, by identifying strategies commonly used with major powers in its treatment of middle and smaller powers. The study period covers the period of Kazakhstan’s independent foreign policy from independence to roughly 2005, and it examines aspects of how its multivector strategy was used and evolved during that time. Through examination and coding of archival materials drawn from the National Archives of the Republic of Kazakhstan, multivectorism is demonstrated to be a prevailing force for the country’s foreign policy and not a bellwether technique deployed against greater powers.
Keywords: Type of access: Open Access; Kazakhstan's Multivectorism